2009
DOI: 10.2174/138945009788488369
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Expression, and Regulation of UDP-GlcNAc: Dolichol Phosphate GlcNAc-1-Phosphate Transferase (DPAGT1)

Abstract: Glycosylation of proteins on asparagine amino acids (N-linked) in proteins of eukaryotic cells is initiated by the biosynthesis of dolichol-pyrophosphate-N-acetylglucosamine from dolichol-phosphate and UDP-N-acetylglucosamine. The enzyme catalyzing this reaction, UDP-GlcNAc:Dolichol Phosphate GlcNAc-1-Phosphate Transferase (DPAGT1), has been further characterized in several cell types with respect to its gene, gene products, membrane topology, functional sites, lipid dependence, and metabolic regulation. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…N-Glycosylation is initiated in the endoplasmic reticulum (ER) by the dolichol phosphate-dependent N -acetylglucosamine 1-phospho-transferase (GPT), encoded by the DPAGT1 gene (Rine et al 1983; Bretthauer 2009; Aebi 2013). GPT catalyzes the transfer of N -acetylglucosamine (GlcNAc) from UDP-GlcNAc to dolichol phosphate to produce dolichol-PP-GlcNAc, which is the first step in the synthesis of a lipid-linked oligosaccharide (LLO) precursor (Figure 1).…”
Section: Dpagt1 As a Key Regulator Of Protein N-glycosylation In Homementioning
confidence: 99%
See 1 more Smart Citation
“…N-Glycosylation is initiated in the endoplasmic reticulum (ER) by the dolichol phosphate-dependent N -acetylglucosamine 1-phospho-transferase (GPT), encoded by the DPAGT1 gene (Rine et al 1983; Bretthauer 2009; Aebi 2013). GPT catalyzes the transfer of N -acetylglucosamine (GlcNAc) from UDP-GlcNAc to dolichol phosphate to produce dolichol-PP-GlcNAc, which is the first step in the synthesis of a lipid-linked oligosaccharide (LLO) precursor (Figure 1).…”
Section: Dpagt1 As a Key Regulator Of Protein N-glycosylation In Homementioning
confidence: 99%
“…DPAGT1 functions at a rate-limiting step in the N-glycosylation pathway, so modest changes in its expression result in robust changes in the N-glycosylation status of proteins (Clark et al 1983; Hayes and Lucas 1983; Welply et al 1985; Meissner et al 1999; Mendelsohn et al 2005; Bretthauer 2009). Human fibroblasts from a patient bearing mutations in both alleles of DPAGT1 display dramatically reduced GPT activity that is associated with diminished levels of LLO and hypo-glycosylation of proteins (Wu et al 2003).…”
Section: Dpagt1 As a Key Regulator Of Protein N-glycosylation In Homementioning
confidence: 99%
“…DPAGT1/GPT, which mediates the first committed step in the N-glycosylation pathway, is a multipass ER membrane protein that catalyzes the transfer of GlcNAc-1-phosphate from UDP-GlcNAc to the lipid carrier dolichol monophosphate (Dol-P) to form N-acetylglucosamine-pyrophosphatidyldolichol (GlcNAc-PP-Dol) (19). DPAGT1/GPT is the first enzyme in a series of 14 ER-associated glycosyltransferases assembling a 14-mer oligosaccharide core that is transferred en bloc onto asparagine residues within potential N-glycosylation sites by the oligosaccharyltransferase (OST) complex (19,20).…”
mentioning
confidence: 99%
“…DPAGT1 encodes the enzyme dolichyl-phosphate-N-acetylglucosamine-phosphotransferase-1, a transmembrane ER protein essential for N-linked glycosylation [47]. A study on five unrelated patients with similar clinical features to GFPT1-CMS identified DAPGT1 as a novel CMS gene [2].…”
Section: Dpagt1mentioning
confidence: 99%